Update on Menopausal Hormone Therapy for Fracture Prevention - Stepan, Jan J; Hruskova, Hana; Kverka, Miloslav (Current osteoporosis reports, 2019)
PURPOSE OF REVIEW: The goal of the review is to assess the appropriateness of menopausal hormone therapy (MHT) for the primary prevention of bone loss in women at elevated risk in the early years after menopause. RECENT FINDINGS: Estrogen alone or combined with progestin to protect the uterus from cancer significantly reduces the risk of osteoporosis-related fractures. MHT increases type 1 collagen production and osteoblast survival and maintains the equilibrium between bone resorption and bone formation by modulating osteoblast/osteocyte and T cell regulation of osteoclasts. Estrogens have positive effects on muscle and cartilage. Estrogen, but not antiresorptive therapies, can attenuate the inflammatory bone-microenvironment associated with estrogen deficiency. However, already on second year of administration, MHT is associated with excess breast cancer risk, increasing steadily with duration of use. MHT should be considered in women with premature estrogen deficiency and increased risk of bone loss and osteoporotic fractures. However, MHT use for the prevention of bone loss is hindered by increase in breast cancer risk even in women younger than 60 years old or who are within 10 years of menopause onset.
Keywords: Osteoporotic Fractures; Postmenopausal osteoporosis; resorpce kosti; Humans; osteogeneze; lidé středního věku; kolagen typu I; Osteogenesis; T-Lymphocytes; osteoporotické fraktury; Osteoporosis, Postmenopausal; osteoblasty; Female; Bone and Bones; Osteocytes; Progestins; Collagen Type I; výsledek terapie; kosti a kostní tkáň; Bone cells; lidé; osteoklasty; Osteoblasts; osteocyty; estrogenní substituční terapie; progestiny; Breast Neoplasms; ženské pohlaví; postmenopauzální osteoporóza; Estrogen Replacement Therapy; Middle Aged; Treatment Outcome; estrogeny; Prevention; nádory prsu; Osteoclasts; T-lymfocyty; Bone Resorption; Risk Assessment; hodnocení rizik; Fracture; Estrogens